Performance of bio-based building materials - Jones, Dennis; Brischke, Christian; ScienceDirect eBooks (Duxford, United Kingdom : Woodhead Publishing, an imprint of Elsevier, 2017)
Performance of Bio-based Building Materials provides guidance on the use of bio-based building materials (BBBM) with respect to their performance. The book focuses on BBBM currently present on the European market. The state-of-the-art is presented regarding material properties, recommended uses, performance expectancies, testing methodology, and related standards. Chapters cover both 'old and traditional' BBBM since quite a few of them are experiencing a comeback on the market. Promising developments that could become commercial in the near future are presented as well. The book will be a valuable reference resource for those working in the bio-based materials research community, architects and agencies dealing with sustainable construction, and graduate students in civil engineering.
3.3 Hemp3.3.1 Introduction; 3.3.2 Morphology of hemp fibres; 3.3.3 Applications of hemp fibres for building materials; 3.3.4 Conclusion; 3.4 Straw; 3.4.1 Structure and composition of straw; 3.4.2 Straw bales as a construction material; 3.4.3 Hygrothermal properties of straw bales; 3.4.4 Mechanical properties of straw bales; 3.4.5 Acoustic properties of straw bale construction; 3.4.6 Fire resistance of straw bale construction; 3.4.7 Compressed straw board; 3.4.8 Conclusion; 3.5 Bamboo and rattan; 3.5.1 Introduction
Includes index.
Online resource; title from PDF title page (EBSCO, viewed July 19, 2017).
Elsevier
Keywords: Building materials; Building materials -- Environmental aspects; Biochemical engineering; TECHNOLOGY & ENGINEERING / Civil / General; Biochemical engineering; Building materials; Building materials -- Environmental aspects; Electronic books